Assessing efforts of the Government of India and the United Nations Office on Drugs and Crime in Tackling Bride Trafficking - Violinda Deda; Mariana E. Buiney; Made Selly D. Suryanti (Cenderawasih University, 2022)
Bride trafficking is a form of human trafficking that severely affects women and girls. Although some literature has described the causes and impacts, there have been relatively few studies to shed light on the efforts to overcome the problem. By using a theoretical framework, this study limits the research scope and defines the specific viewpoint to analyse the topic. This article aims to examine the efforts of the government of India and the United Nations Office on Drugs and Crime (UNODC) in combating bride trafficking. It pinpoints the causes of bride trafficking in India, such as economic demands, the poverty level, high demand for dowry, the practice of foeticide, and social marginalization leading victims to re-trafficking, as well as the impacts: physical and mental health problems, social exclusion, infectious diseases, and the damage to India’s reputation. This article found that the government of India and UNODC has been relatively effective in handling bride trafficking. The number of trafficked women (victims) cases in India declined significantly between 2016 and 2020. The UNODC also plays a pivotal role in strengthening the law enforcement capacity of the government of India. KEYWORDSBride Trafficking; Government of India; UNODC